Analisis Pemasaran Durian di Desa Talang Mulya Kabupaten Pesawaran - Any Eliza (Jurnal Ilmiah ESAI, 2016)
Indonesia is one of the producers of durian fruit, but compared to other durian producing countries, namely Thailand and Malaysia, Indonesia durian production is quite low (500-700 thousand tons per year). Although the durian is attractive to many people, but durian farmer's profits can be considered low. This study aims to analyze channel of marketing, marketing margin and marketing efficiency of durian in Talang Mulya as one of the durian producers in Lampung Province. The research conducted from April to June 2015. The data were processed with qualitative and quantitative analysis. The sampling was done to 30 farmers, 8 retailers and10 customers by purposive sampling. The results showed that there are four marketing channels durian in Talang Mulya village, ie channel 1: farmer-traders-consumers, channel 2: farmer- traders-retailer-consumer, channel 3: farmer-retailer-consumer and channel 4: farmers - consumer. Marketing margin analysis found that the marketing agencies that earn the highest profit is the retailer. The results show that channel 4 is the most efficient marketing channel for marketing costs born by the consumer is smaller compared to other marketing channels.Â Keywords: durian, marketing channel, marketing margins, marketing efficiency